2016
DOI: 10.3389/fpls.2016.01641
|View full text |Cite
|
Sign up to set email alerts
|

Variance, Genetic Control, and Spatial Phenotypic Plasticity of Morphological and Phenological Traits in Prunus spinosa and Its Large Fruited Forms (P. x fruticans)

Abstract: Prunus spinosa is a highly esteemed shrub in forest and landscape plantings. Shrubs with larger organs occur often and are considered either as large fruited forms of P. spinosa or as P. x fruticans, involving a hybridization process with the ancient cultivated P. insititia (crop-to-wild gene flow). As climate change may augment hybridization processes in the future, a hybrid origin is important to detect. In addition, studying crop-to-wild gene flow can give insights in putative consequences for the wild popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…A detailed morphological and phenological analysis (Vander Mijnsbrugge et al 2016) and breeding tests (Woldring 1997/1998) of the P. spinosa – P . × fruticans complex showed that the latter taxon is certainly a hybrid of blackthorn and cultivated plums as a result of various crossings.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed morphological and phenological analysis (Vander Mijnsbrugge et al 2016) and breeding tests (Woldring 1997/1998) of the P. spinosa – P . × fruticans complex showed that the latter taxon is certainly a hybrid of blackthorn and cultivated plums as a result of various crossings.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this complexity and recurrent hybridizations and/or allopolyploidy phenomena, taxonomy has been controversial until recent times [3,44], and phylogenetic studies, both with nuclear and chloroplast approaches, have recently revealed an intricate evolutionary history of the genus along with close, but conflicting, relationships among and within subgenera [1, 42,[45][46][47].…”
Section: Prunus Taxonomy Species Identification and Diversitymentioning
confidence: 99%
“…Rosaceae, Fagaceae and Rubiaceae are among the preferred families of plants consumed by ungulates (Gebert and Verheyden-Tixier 2001;Storms et al 2008;Freschi et al 2021). The genus Prunus L. (Rosaceae) includes over 200 species of trees and shrubs (Arnold Arboretum, 1940), some of which are commercially important (Veličković et al 2021), are used in the restoration of historical landscapes (Mijnsbrugge et al 2016;Mijnsbrugge et al 2022) and boost species diversity by providing appropriate foraging and habitat resources for wildlife (Popescu and Caudullo 2016). A general characteristic of plants of the genus Prunus is that they contain carbon (C)-and N-rich defensive compounds (Santos Pimenta et al 2014;Peschiutta et al 2018), and also Ca-based inducible defence mechanisms such as calcium oxalate crystals (COC) (Peschiutta et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Blackthorn Prunus spinosa is one of the most widespread and common wild shrub species in Europe (Mijnsbrugge et al 2016), occurring mainly in central and western parts of the continent with range limits in southern Scandinavia, Asia Minor, Caucasus and North Africa (Seneta and Dolatowski 1997;Popescu and Caudullo, 2016). The species is commonly found along the margins of deciduous forests, as a component of thermophilous communities, and as one of the successional species along former meadows and arable fields (Szafer and Zarzycki 1977;Seneta and Dolatowski 1997;Popescu and Caudullo 2016).…”
Section: Introductionmentioning
confidence: 99%